2020
DOI: 10.1111/dth.14066
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness and safety of ixekizumab in psoriasis patients under clinical practice conditions: A Spanish multicentre retrospective study

Abstract: The objective of the study was to evaluate efficacy and safety of ixekizumab in psoriasis patients under clinical practice conditions. Observational, retrospective, multicentre study that included patients with ixekizumab from March 2017 to March 2019. ≥ 90% reduction in the Psoriasis Area and Severity Index (PASI 90) and absolute PASI <2 were the parameters used to assess treatment response. Adverse events (AEs) were collected. Of the 301 patients included, 111 were women (36.9%), mean age was 48.5 (±13.5) ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 15 publications
5
6
1
3
Order By: Relevance
“…with RCTs, but PASI90 response rates (86.1%) were higher at week 16. Age, sex, duration of psoriasis, and baseline PASI scores of the patients in our cohort were similar to those in other studies [15][16][17][18][19][20][21] bio-naive (19.3%) and bio-experienced (80.3%) patients at week 12 were higher in the bio-experienced group (76.1% vs. 67.7%) without significant difference. 23 Interestingly, most of the RWD has shown that a prior biologic agent treatment failure negatively affects ixekizumab response.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…with RCTs, but PASI90 response rates (86.1%) were higher at week 16. Age, sex, duration of psoriasis, and baseline PASI scores of the patients in our cohort were similar to those in other studies [15][16][17][18][19][20][21] bio-naive (19.3%) and bio-experienced (80.3%) patients at week 12 were higher in the bio-experienced group (76.1% vs. 67.7%) without significant difference. 23 Interestingly, most of the RWD has shown that a prior biologic agent treatment failure negatively affects ixekizumab response.…”
Section: Discussionsupporting
confidence: 88%
“…23 Interestingly, most of the RWD has shown that a prior biologic agent treatment failure negatively affects ixekizumab response. 15,17,18,20 Our findings support earlier RWD that biologic-naive patients had a higher PASI 90 response rate (90.9% vs. 61.5%) at week 16. Participation of biologic-naive patients (80.3%) in our study is similar to the study conducted by Damiani et al 16 ; however, the aforementioned study did not an- Obesity was the most common comorbidity in our patient cohort.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Clinical trial data are obtained under conditions distinct from those found in routine clinical practice. Authors studying the realworld use of various drugs have observed that the patient population in clinical practice has different characteristics to that of clinical trials 8,9 and, in some cases, the outcomes observed in registry data are different from those reported in clinical trials. 10 For this reason, data on the use of a drug in a real-world setting help clinicians to predict how it will work in the patients they attend in their practice.…”
Section: Introductionmentioning
confidence: 99%